اثر تمارین خاصة وفق بعض المتغیرات البیوكینماتیكیة لتطویر بعض القدرات الحركیة و دقة و قوة اداء مھارة الضربة الارضیة الامامیة في التنس الارضي - حسناء ستار جبار; محمد حسن هليل (physical education and sport sciences college for women/ Baghdad University, 2014)
Tennis games that are their skills are different and require the player to move quickly and gracefully and hit the ball the terms Bio-kinematcal correctly to achieve the goal of skill highest accuracy and strength , the goal of research is to identify the effect of specific exercises according to some variables Bio-kinematcal to develop some motor skills , accuracy and power performance of the skill of the strike front in tennis has sample consisted of (8) players of the national team of Iraq tennis . most important conclusions was that the special exercises used have had influence in the development of motor skills of responding kinetic and agility , flexibility and compatibility between the eye and the man had to exercises own according to some variables Bio-kinematcal influence in the development of precision The strike force skill forehand ground